Early Hepatocellular Carcinoma: Transplantation versus Resection: The Case for Liver Resection - Nishant Merchant; Calvin S. David; Steven C. Cunningham (International Journal of Hepatology)
The optimal surgical treatment of hepatocellular carcinoma on well-compensated cirrhosis is controversial. Advocates of liver transplantation cite better long-term survival, lower risk of recurrence, and the ability of transplantation to treat both the HCC and the underlying liver cirrhosis. Transplantation, however, is not universally available to all appropriate-risk candidates because of a lack of sufficient organ donors and in addition suffers from the disadvantages of requiring a more complex pre- and postoperative management associated with risks of inaccessibility, noncompliance, and late complications. Resection, by contrast, is much more easily and widely available, avoids many of those risks, is by many accounts as effective at achieving similar long-term survival, and still allows for safe, subsequent liver transplantation in cases of recurrence. Here, arguments are made in favor of resection being easier, safer, simpler, and comparably effective in the treatment of HCC relative to transplantation, and therefore being the optimal initial treatment in cases of hepatocellular carcinoma on well-compensated cirrhosis.